Prognostic value of pre-treatment 18F-FDG PET uptake for nasopharyngeal carcinoma - ADLI, MUSTAFA (Springer-Verlag Italia s.r.l., 2017)
Purpose: To evaluate the prognostic value of maximal standardized uptake values (SUVmax) from serial fluor-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) in patients with nasopharyngeal carcinoma (NPC). Materials and methods: Fifty-two patients with NPC who underwent 18F-FDG PET/CT scan before radiotherapy with/without chemotherapy were reviewed retrospectively. Twenty-seven patients (52%) were applied 3-D conformal radiotherapy and 25 patients (48%) applied intensity-modulated radiotherapy (IMRT). Fourteen (27%) patients were given neoadjuvant chemotherapy and forty-four (84.6%) patients were given concomitant and adjuvant chemotherapy. Results: Median follow-up time was 34 months (range 5.6–66.4 months). Forty-four (84.6%) patients were alive at last follow-up and eight (15.4%) had died. The best cut-off value of the SUVmax for the primary tumor site (SUVmax-PT) was 13 and 9 for the lymph nodes (SUVmax-LN). Patients with SUVmax-PT ≥ 13.0 and SUVmax-LN ≥ 9 had a significantly higher risk for the development of the distant metastases (p = 0.044 and p = 0.038). DFS was affected in patients with SUVmax-PT ≥ 13 (log rank χ2 = 2.54, p = 0.017) and was significantly lower in patients with SUVmax-LN ≥ 9 for the lymph nodes (log rank χ2 = 5.81, p = 0.013). OS was not affected by SUV levels. A multivariate Cox proportional hazard model of DFS included age (≥ 40), SUVmax-LN (< 9), T stage (T1–2) and neoadjuvant chemotherapy are significantly better prognosis for the DFS. Conclusion: 18F-FDG PET/CT uptake before treatment, as determined by SUVmax, may be a valuable tool to evaluate prognosis in NPC patients. © 2017 Italian Society of Medical Radiology
Keywords: Nasopharyngeal carcinoma; PET/CT; Prognosis; Radiotherapy; SUVmax